Optical networks a practical perspective - Ramaswami, Rajiv; Sivarajan, Kumar N. (San Francisco : Morgan Kaufmann Publishers, 2002)
This fully updated and expanded second edition of Optical Networks: A Practical Perspective succeeds the first as the authoritative source for information on optical networking technologies and techniques. Written by two of the field's most respected individuals, it covers componentry and transmission in detail but also emphasizes the practical networking issues that affect organizations as they evaluate, deploy, or develop optical solutions. This book captures all the hard-to-find information on architecture, control and management, and other communications topics that will affect you every step of the way-from planning to decision-making to implementation to ongoing maintenance. If your goal is to thoroughly understand practical optical networks, this book should be your first and foremost resource. * Focuses on practical, networking-specific issues: everything you need to know to implement currently available optical solutions. * Provides the transmission and component details you need to understand and assess competing technologies. * Offers updated and expanded coverage of propagation, lasers and optical switching technology, network design, transmission design, IP over WDM, wavelength routing, optical standards, and more.
Introduction to optical networks -- Propagation of signals in optical fiber -- Components -- Modulation and demodulation -- Transmission system engineering -- Client layers of the optical layer -- WDM network elements -- WDM network design -- Control and management -- Network survivability -- Access networks -- Photonic packet switching -- Deployment considerations.
Includes bibliographical references and index.
Keywords: Optical communications; Fiber optics; Electronic books